4 is the constant varriation
B. He received 29% discount on the car.<span />
Answer:
.
Step-by-step explanation:
If f(x) = (6x-11), then f(-6) = -47.
We are provided in the question statement with a function "f(x)" whose output is a polynomial of 1 variable and degree 1.
To obtain the value of f(-6) from the output polynomial of the function f(x), we will simply need to substitute (-6) as the value of x in the polynomial and calculate the final value.
So,
![f(-6)=[(6*(-6))-11]\\or, f(-6)=(-36-11)\\or, f(-6)=-(36+11)\\or, f(-6) =-47](https://tex.z-dn.net/?f=f%28-6%29%3D%5B%286%2A%28-6%29%29-11%5D%5C%5Cor%2C%20f%28-6%29%3D%28-36-11%29%5C%5Cor%2C%20f%28-6%29%3D-%2836%2B11%29%5C%5Cor%2C%20f%28-6%29%20%3D-47)
Hence, f(-6) = -47.
- Polynomial: In mathematics, an expression of more than two algebraic terms, especially the sum of several terms that contain the same variable(s) of different powers and individual, distinct co-efficients.
- Function: In Mathematics, a function is an operator which on taking input, provides a certain output.
To learn more about Polynomials and Functions, click on the link below.
brainly.com/question/26910958
#SPJ9
Answer:
Step-by-step explanation:
3.5 pounds × $0.98/pound = $3.43